Comparative analysis of the regulations against sexual harassment in public universities in Central America - García Zamora, Éricka (2025)
The objective of the article is to compare the regulations on sexual harassment of the main public universities of Guatemala, Honduras, El Salvador, Nicaragua, Costa Rica and Panama, in order to establish their scope in three central lines: a) existence of a specific regulation on this type of violence, b) conceptualization of sexual harassment and, c) evaluation of the established mechanisms in relation to the model or vision of the prevailing legal approach regarding the rights of victims, the statute of limitations for this crime and finally, the conditions for the elevation and ratification of the complaints submitted. The methodological approach is qualitative, and the research is documentary based on primary sources related to the standards and protocolspromulgated in HEIs and secondary sources. The research is limited to the period 1996-2020. It is concluded that the existing regulations respond to a guaranteed model of disciplinary procedures that does not consider the variable sex or the asymmetry of the relationships between the parties involved.